UJI EFEKTIVITAS FUNGISIDA DAN EKSTRAK KACANG HIJAU DALAM AKLIMATISASI ANGGREK Dendrobium Phalaenopsis Fitzg. YANG TERKONTAMINASI : TESTING THE EFFECTIVENESS OF FUNGICIDES AND MUNG BEAN EXTRACT IN THE ACCLIMATIZATION OF CONTAMINATED Dendrobium Phalaenopsis Fitgz. ORCHIDS - Silvia Mona Fitri; Ni Luh Arpiwi; Martin Joni (SIMBIOSIS, 2025)
Orchid plants are difficult to develop naturally and often require human assistance, one method being through tissue culture. Tissue culture has limiting factors, such as contamination by microbes. This study aims to determine the optimal soaking time in fungicide to eliminate fungal contamination and to find the best concentration of mung bean extract for the growth of Dendrobium larat orchids. This experimental research uses a completely randomized factorial design with 2 factors, comprising 12 treatment combinations and 3 repetitions.The first factor is the duration of fungicide soaking at 0 minutes, 30 minutes, and 60 minutes in an antracol fungicide solution at a dose of 1.50 g/L. The second factor is the addition of mung bean extract at 0 g/L, 50 g/L, 70 g/L, and 90 g/L. The best fungicide soaking duration was found to be 60 minutes. The measurable parameters showed that the highest plant growth and the longest root length occurred with fungicide soaking for 60 minutes and the addition of mung bean extract at a concentration of 70 g/mL. The highest number of leaves was observed with fungicide soaking for 60 minutes and the addition of mung bean extract at a concentration of 50 g/mL. Keywords: Dendrobium larat, antracol, decontamination